2021
DOI: 10.1186/s42501-021-00103-2
|View full text |Cite
|
Sign up to set email alerts
|

First record of stable isotopes (δ13C, δ18O) and element ratios (Mg/Ca, Sr/Ca) of Middle to Late Jurassic belemnites from the Indian Himalayas and their potential for palaeoenvironmental reconstructions

Abstract: Middle to Late Jurassic belemnites from the Spiti and Zanskar valleys in the Indian Himalayas were used for stable isotope (δ13C, δ18O) and element (Mg/Ca, Sr/Ca) analyses. Although the Himalayan orogeny deformed and altered a large portion of the collected fossils, cathodoluminescence and scanning electron microscopy in combination with analyses of iron and manganese contents allowed the identification of belemnites believed to still retain their original chemical composition. Results indicate a long-term tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 82 publications
0
5
0
1
Order By: Relevance
“…The dominance of black shale with occasional calc-arenite beds in F.A-II suggests greater depth than the F.A-I, where the planar laminated shale deposited from suspension falls out in a calm and quiet environment. The earlier studies on palaeoredox suggested that the depositional site was dysoxic-anoxic (Fursich et al 2021; Albert et al 2021). The absence of coarse-grained sediment in an anoxic zone infers depositional site below the wave and storm base.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The dominance of black shale with occasional calc-arenite beds in F.A-II suggests greater depth than the F.A-I, where the planar laminated shale deposited from suspension falls out in a calm and quiet environment. The earlier studies on palaeoredox suggested that the depositional site was dysoxic-anoxic (Fursich et al 2021; Albert et al 2021). The absence of coarse-grained sediment in an anoxic zone infers depositional site below the wave and storm base.…”
Section: Discussionmentioning
confidence: 99%
“…The Himalayan sedimentary succession deposited along the north-eastern boundary of India in the southern hemisphere of Tethys holds crucial information on Eocambrian to Eocene (Fig. 2a; Bhargava and Singh, 2019; Fursich et al 2021; Albert et al 2021; Sun et al 2021). The Jurassic succession is mainly preserved at the inner part of the higher Himalayas, often representing the scenario during Gondwana’s disintegration.…”
Section: Geological Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…The Spiti area at the northern margin of the Indian craton bordering the Neotethys during the Late Jurassic occupied a southern palaeolatitude between 20-30° according to the Paleolatitude Calculator of van Hinsbergen et al (2015). The occurrence of high latitude southern taxa at relatively low latitudes can be explained by their restriction to outer shelf and slope environments where, due to upwelling, lower water temperatures prevailed (compare Alberti et al 2021;Fürsich et al 2021). In this context, isothermal submergence may explain the way polar faunas were able to cross the tropics (e.g., Crame 1993).…”
Section: Order Pectinida Gray 1854 Family Buchiidae Cox 1953mentioning
confidence: 99%
“…Because of the key role of ancient shells and shell fossils in the reconstruction of past climate conditions, they have long been a matter of interest to geological Vernal et al 1992;Geary et al 1992;Goodwin et al 2001;Ullmann et al 2017;Killam & Clapham 2018;Scholz et al 2020;Morán et al 2021), archaeological studies (Quitmyer et al 1997;Leng & Lewis 2016). Indeed, one of the main motivations for the study of bivalves (Müller et al 2017;Huyghe et al 2020;Das et al 2021;Kelemen et al 2021;), gastropods (Cespuglio et al 1999;García-Escárzaga et al 2019;Irie & Suzuki 2020), and extinct species such as belemnites Urey et al 1951;Alberti et al 2021) is to gain insight into climatic conditions.…”
Section: Introductionmentioning
confidence: 99%